Glamour in a golden age : movie stars of the 1930s - McLean, Adrienne L.; Becker, Christine; Castonguay, James; Creekmur, Corey K.; Desjardins, Mary; Doty, Alexander; Fischer, Lucy; Fuller-Seeley, Kathryn; Hark, Ina Rae; Knee, Adam; Larson, Allen; Lugowski, David; et al. (Star decades: American culture/American cinema., 2011)
Shirley Temple, Clark Gable, Errol Flynn and Olivia de Havilland, Fred Astaire and Ginger Rogers, Bette Davis, Joan Crawford and Norma Shearer, Marlene Dietrich and Greta Garbo, William Powell and Myrna Loy, Jean Harlow, and Gary Cooper--Glamour in a Golden Age presents original essays from eminent film scholars that analyze movie stars of the 1930s against the background of contemporary American cultural history.